Effect of Chitosan on Biochemical, Microbiological and Sensory Characteristics of Restructured Products from Pangasius (Pangasianodon hypophthalmus) - Jeyakumari, A.; Ayoob, K. S.; Ninan, George; Zynudheen, A. A.; Joshy, C. G.; Lalitha, K.V. (Fishery Technology, 2016)
In India, pangasius (Pangasianodon hypophthalmus) farming is gaining importance among the farmers due to its fast growth and better survival rate. In the present study, restructured products were prepared from pangasius mince in four different formulations by using pangasius fish mince, corn starch (4%) and chitosan (0.75%). Formulation containing only corn starch (4%) served as control. Shelf life of the products was evaluated under chilled (2ÂºC) condition up to 17 days. Biochemical quality parameters viz., total volatile base nitrogen (TVB-N), free fatty acid (FFA) and peroxide value (PV), thiobarbituric acid (TBA) value were within acceptable limits in chitosan treated samples. Control sample was acceptable only upto 6 days compare to 12 days in chitosan treated samples.